Choice of prioritization method impacts recommendations for climate‐informed bird conservation in the United States. Issue 12 (19th October 2022) - Taylor, Lotem; Saunders, Sarah P.; Wu, Joanna X.; Bateman, Brooke L.; Grand, Joanna; DeLuca, William V.; Wilsey, Chad B.
Abstract : Climate‐informed spatial planning is urgently needed to guide initiatives aimed at both conserving biodiversity as a whole (e.g. protection of 30% of lands and waters by 2030) and recovering North American avifauna in particular. Various methods for prioritizing conservation areas exist, yet alternative methods may direct managers to different lands for protection, and thus varying recommendations for meeting area‐based targets. Here, we used bird species distribution models and landcover projections to systematically evaluate two widely used methods for prioritizing areas most likely to facilitate the persistence of multiple species under climate change: 1) in situ macrorefugia, identified as areas of high predicted species retention; and 2) complementarity‐based optimizations, identified using the Zonation conservation planning software. For 17 biogeographical groups in the continental United States, we compared priority areas for bird conservation derived from these two alternatives with respect to their spatial distributions and consensus (i.e. overlap), expected conservation outcomes (e.g. species and functional diversity), predicted climate change exposure, habitat characteristics, landscape configurations and degree of formal protection. Spatial distributions of priority areas differed by biogeographical group and method, with 40.5% consensus on average across groups. Consensus was extensive within mountainous and coastal regions, and limited at high latitudes (e.g. Alaska) and in flat, interior regions (e.g. grasslands). As expected, complementarity‐based optimizations more efficiently represented species than retention‐based in situ macrorefugia, especially for forest groups, and had greater overall biodiversity value and better habitat condition. Conversely, in situ macrorefugia encompassed higher elevations and larger contiguous patches and were expected to experience less winter‐season warming. Formal protection averaged < 50% across biogeographical groups, regardless of prioritization method. Our findings illustrate the value of complementarity‐based optimizations for bird conservation under climate change. More broadly, comparing approaches for prioritizing areas for long‐term species persistence can reveal critical trade‐offs in recommendations for climate‐informed protected area planning.